2019
DOI: 10.3390/s19235295
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Determination of Nitrogen, Phosphorus and Potassium Contents in Greenhouse Tomato Plants Based on Multispectral Three-Dimensional Imaging

Abstract: Measurement of plant nitrogen (N), phosphorus (P), and potassium (K) levels are important for determining precise fertilization management approaches for crops cultivated in greenhouses. To accurately, rapidly, stably, and nondestructively measure the NPK levels in tomato plants, a nondestructive determination method based on multispectral three-dimensional (3D) imaging was proposed. Multiview RGB-D images and multispectral images were synchronously collected, and the plant multispectral reflectance was regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
(61 reference statements)
2
8
0
3
Order By: Relevance
“…Additionally, it has leveling screws on the four legs of the platform, in order to adjust the inclination of the mechanical structure. In comparison with the structures in other investigations (Thapa et al [19], Sun et al [12,20], Zhang et al [15]), the proposed structure (shown in Figure 2) is able to freely move both the sensors and the rotating base over the rails system allowing the phenotyping of plants with a height up to 2.5 m, regardless of their structure. ), the proposed structure (shown in Figure 2) is able to freely move both, the sensors and the rotating base over the rails system allowing the phenotyping of plants with a height up to 2.5m, regardless their structure.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, it has leveling screws on the four legs of the platform, in order to adjust the inclination of the mechanical structure. In comparison with the structures in other investigations (Thapa et al [19], Sun et al [12,20], Zhang et al [15]), the proposed structure (shown in Figure 2) is able to freely move both the sensors and the rotating base over the rails system allowing the phenotyping of plants with a height up to 2.5 m, regardless of their structure. ), the proposed structure (shown in Figure 2) is able to freely move both, the sensors and the rotating base over the rails system allowing the phenotyping of plants with a height up to 2.5m, regardless their structure.…”
Section: Methodsmentioning
confidence: 87%
“…x + y = 0 (11) With Equation ( 11) of the XY plane of reference of the sensors, the unit vector B that is normal to the plane can also be found, as presented in Equation (12).…”
Section: Sensory Fusion Between Point Clouds and Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other detection systems include and optical and thermal sensors. The optical sensors which include absorbance, reflectance, luminescence, and surface plasmon resonance techniques [ 138 ] are nondestructive methods based on multispectral three-dimensional (3D) imaging [ 139 ]. The fertilizer application and irrigation water were optimized based on the reflectance characteristics of the canopy such as leaf temperature, leaf relative water content, and leaf chlorophyll content in the field of tomato [ 138 ].…”
Section: The Fourth Industrial Revolution In Packaging and Tomato mentioning
confidence: 99%
“…Vazquez-Arellano et al 15 considered ICP algorithm to reconstruct the 3D model of maize plants, and its reconstruction effect is pleasing, but the amount of calculation is too large during registration. Sun et al 16 chose ICP algorithm for the precise registration and reconstruction of multi-spectral 3D point cloud model of plants. However, the direct use of the ICP algorithm for point cloud registration will increase the amount of calculation and make the ICP algorithm become a local optimization, and eventually lead to the registration error being too large to meet the accuracy requirements 17 .…”
Section: Introductionmentioning
confidence: 99%